Low cycle fatigue behavior and deformation mechanism of different microstructures in Ti-5Al-5Mo-5V-3Cr alloy. (July 2021) - Sen, Mainak; Suman, Swati; Mukherjee, Shreya; Banerjee, Trideep; Sivaprasad, S; Tarafder, Soumitra; Bhattacharjee, Amit; Kumar Kar, Sujoy
Highlights: LCF of Bimodal and β annealed microstructures of Ti5553 alloy having similar YS. Higher life of β annealed structure explained by crack-microstructure interaction. Microstructural constituents deformed in different sequence for the two structures. Underlying Deformation mechanisms explained the relative softening responses. Abstract: Two fundamental questions have been addressed on a recently developed high strength β Ti alloy, Ti-5Al-5V-5Mo-3Cr, with respect to two very different types of microstructures, one bimodal and the other fully lamellar, both having similar yield strength. Those are: 1) If and what would be the difference in their LCF response? 2) What would be the sequence of plastic deformation among the phases of different morphology, β, globular α and lath α? TEM based deformation micro mechanism explained the LCF response at various strain amplitudes. Crack path-microstructure interaction explained the difference in life, specifically observed at low strain amplitude.